THE EFFECT OF WORKING CAPITAL MANAGEMENT ON PROFITABILITY IN MANUFACTURING COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE - Mis F Situmeang; Fisy Amalia; Loso Judijanto (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This research aims to analyze the effect of working capital management on profitability in manufacturing companies listed on the Indonesia Stock Exchange. Optimal working capital is one of the key factors to achieve a balance between liquidity and profitability. This research includes an analysis of the main components of working capital, namely accounts receivable, inventory and accounts payable, as well as how each component contributes to increasing or decreasing company profitability. Through a literature review, data from manufacturing company financial reports during a certain period was taken and analyzed using the linear regression method. The results of the analysis show that efficient management of accounts receivable, inventory optimization and good debt management significantly increase the company's profitability. In addition, it was found that companies that are able to adjust working capital policies in accordance with market dynamics tend to have more stable and profitable financial performance. These findings emphasize the importance of strategic working capital management in achieving company financial goals. Effective working capital management not only increases profit margins but also strengthens a company's competitive position in the manufacturing industry. Therefore, companies must continue to implement adaptive policies and adopt advanced technology to improve operational efficiency in managing working capital.